Key Expansion in Block Stochastic Algorithms - Chugunkov, Ilya V.; Markova, Daria A.; Boronin, Rostislav V.; Kurochkina, Maria-Anastasia A.; Fedotova, Vera A. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2024)
This article is devoted to the issue of increasing the efficiency of block algorithms by expanding the size of the key space. Existing approaches to key deployment are analyzed, and a key deployment algorithm with customizable parameters is proposed. The statistical properties of the proposed solution are evaluated, and the applicability of this approach in low-resource cryptography is considered.